Calculati: (2^3×3^2×5^4)×(2^4×3^5×5^3):(2^6×3^6×5^6)
Am nevoie urgent!
Răspunsuri la întrebare
Răspuns de
1
(2^3×3^2×5^4)×(2^4×3^5×5^3):(2^6×3^6×5^6) =
2^7 x 3^7 x 5^7 / 2^6 x 3^6 x5^6 =
2^(7-6) x 3^(7-1) x 5^(7-1) =
2 x 3 x 5 =
6 x 5 =
30
2^7 x 3^7 x 5^7 / 2^6 x 3^6 x5^6 =
2^(7-6) x 3^(7-1) x 5^(7-1) =
2 x 3 x 5 =
6 x 5 =
30
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Istorie,
8 ani în urmă
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă